Do inositol supplements enhance phosphatidylinositol supply and thus support endoplasmic reticulum function?. Issue 3 (3rd June 2018) - Michell, Robert H.
Abstract: This review attempts to explain why consuming extra myo inositol (Ins), an essential component of membrane phospholipids, is often beneficial for patients with conditions characterised by insulin resistance, non-alcoholic fatty liver disease and endoplasmic reticulum (ER) stress. For decades we assumed that most human diets provide an adequate Ins supply, but newer evidence suggests that increasing Ins intake ameliorates several disorders, including polycystic ovary syndrome, gestational diabetes, metabolic syndrome, poor sperm development and retinopathy of prematurity. Proposed explanations often suggest functional enhancement of minor facets of Ins Biology such as insulin signalling through putative inositol-containing 'mediators', but offer no explanation for this selectivity. It is more likely that eating extra Ins corrects a deficiency of an abundant Ins-containing cell constituent, probably phosphatidylinositol (PtdIns). Much of a cell's PtdIns is in ER membranes, and an increase in ER membrane synthesis, enhancing the ER's functional capacity, is often an important part of cell responses to ER stress. This review: (a) reinterprets historical information on Ins deficiency as describing a set of events involving a failure of cells adequately to adapt to ER stress; (b) proposes that in the conditions that respond to dietary Ins there is an overstretching of Ins reserves that limits the stressed ER's ability to make the 'extra' PtdIns needed for ER membrane expansion; and (c) suggests that eating Ins supplements increases the Ins supply to Ins-deficient and ER-stressed cells, allowing them to make more PtdIns and to expand the ER membrane system and sustain ER functions.